Lifelong Learning as Metaphor: Researching Policy in the Education of Adults - Katherine Nicoll (Adult Education Research Conference, 2000)
Analysts of policy have hitherto not paid much attention to how policy language acts to build up representations of reality. This paper agues for the usefulness of a discursive approach to policy analysis, and illustrates it in the context of emerging policies for ‘lifelong learning’.